2019
DOI: 10.1111/bph.14867
|View full text |Cite
|
Sign up to set email alerts
|

Isoniazid and host immune system interactions: A proposal for a novel comprehensive mode of action

Abstract: The known mode of action of isoniazid (INH) is to inhibit bacterial cell wall synthesis following activation by the bacterial catalase-peroxidase enzyme KatG in Mycobacterium tuberculosis (Mtb). This simplistic model fails to explain (a) how isoniazid penetrates waxy granulomas with its very low lipophilicity, (b) how isoniazid kills latent Mtb lacking a typical cell wall, and (c) why isoniazid treatment time is remarkably long in contrast to most other antibiotics. To address these questions, a novel comprehe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…Furthermore, according to the calculated LogP values, the compounds are highly lipophilic compared to INH (LogP = −0.35, calculated in SwissADME). Besides mutations in either katG or the inhA promoter, this low hydrophobicity of INH is linked to the long duration of TB treatment [ 32 ]. The mycolic acid outer layer of Mtb is so lipophilic that INH cannot efficiently penetrate and cross it.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, according to the calculated LogP values, the compounds are highly lipophilic compared to INH (LogP = −0.35, calculated in SwissADME). Besides mutations in either katG or the inhA promoter, this low hydrophobicity of INH is linked to the long duration of TB treatment [ 32 ]. The mycolic acid outer layer of Mtb is so lipophilic that INH cannot efficiently penetrate and cross it.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, this type of process provides chances for M. tuberculosis to manipulate autophagy. Studies have revealed that once innate immune cells are phagocytized by M. tuberculosis , the proton pump on the cell membrane decreases due to the influence of the bacterial surface proteins, resulting in the reduction of H + influx and a less acidic environment, which provides a suitable environment for M. tuberculosis parasitization ( Khan et al, 2019 ). Another study showed that after invading the human body, M. tuberculosis leads to a fat metabolism disorder in macrophages, and the abnormally increased lipid droplet ingestion by autophagosomes was found to co-locate with M. tuberculosi s and become the nutrient source for its long-term parasitism ( Ouimet et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although immune priming is advantageous in terms of survival ability, its expression could be costly for individuals, particularly when it relies on the long-lasting sustained immune response ( Moret 2003 ; Contreras-Garduño et al 2014 , 2019 ; Coustau et al 2016 ; Shikano et al 2016 ; Khan et al 2019 ). According to the theory of life-history traits, organisms must allocate their limited energy to different biological functions by making trade-offs.…”
Section: Introductionmentioning
confidence: 99%